Youth-Friendly City: Community Center as a Recovery Place for Youth Depression - Abigail, Caroline; Srinaga, Felia; Dewi, Julia (Talenta Publisher, 2025)
Depression is a mental disorder that causes negative feelings on a person's mood, thoughts, behavior, and physical health. There are 3 levels of depression, namely mild, moderate, and severe depression. Depression can be experienced by all age groups. There are 6.2% of Indonesian adolescents aged 15-24 years who are depressed and 91% of them are depressed sufferers who do not take medication or undergo medical treatment. Awareness of mental health in Indonesia is still low and there is still a negative stigma in society towards people including teenagers who are depressed, making the city less friendly for depressed adolescents. The current Covid-19 period has also made adolescents experience mild to moderate depression. The existence of a Community Center for depressed adolescents as a place for them to gather and do activities that can help depression recovery is important. First, the researcher conducted a theoretical study and found 10 recovery environment variables that can help recovery, namely: 1) Privacy, Personal Space, and Density, 2) Security and Restorative, 3) Organization and Independence, 4) Sensory Consideration and Awareness, 5) Comfortable and Homelike Environment, 6) Social Interaction, 7) Nature, Daylight, and Connectedness, 8) Positive Distractions, 9) Goals, 10) Physical Activity. Then from the analysis of precedent studies and the distribution of space atmosphere preference questionnaires, it was found that the incorporation of criteria between space programs is important to create a home-like atmosphere. This study also produced three main strategies that became the basis for designing a community center as a place of recovery that suits the needs of depressed adolescents.